2017
DOI: 10.1038/s41598-017-11210-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ageing and adrenergic challenge on electrocardiographic phenotypes in a murine model of long QT syndrome type 3

Abstract: Long QT Syndrome 3 (LQTS3) arises from gain-of-function Nav1.5 mutations, prolonging action potential repolarisation and electrocardiographic (ECG) QT interval, associated with increased age-dependent risk for major arrhythmic events, and paradoxical responses to β-adrenergic agents. We investigated for independent and interacting effects of age and Scn5a+/ΔKPQ genotype in anaesthetised mice modelling LQTS3 on ECG phenotypes before and following β-agonist challenge, and upon fibrotic change. Prolonged ventricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…77 Similarly, in a Scn5a + / KPQ murine model of LQTS3, dobutamine sympathetic stimulation reduced the incidence of repolarization alternans. 94 Thus, decreased TDR following adrenergic stimulation in LQTS3 suppresses the development of an arrhythmic substrate. Therefore, clinical and experimental data appear to suggest that sympathetic stimulation results in a decrease in both arrhythmic trigger and substrate, and hence decreases the risk of cardiac arrhythmias.…”
Section: Lqts3mentioning
confidence: 99%
See 4 more Smart Citations
“…77 Similarly, in a Scn5a + / KPQ murine model of LQTS3, dobutamine sympathetic stimulation reduced the incidence of repolarization alternans. 94 Thus, decreased TDR following adrenergic stimulation in LQTS3 suppresses the development of an arrhythmic substrate. Therefore, clinical and experimental data appear to suggest that sympathetic stimulation results in a decrease in both arrhythmic trigger and substrate, and hence decreases the risk of cardiac arrhythmias.…”
Section: Lqts3mentioning
confidence: 99%
“…However, some studies contradicting this conclusion have reported that sympathetic activity may be without effect, or may even be proarrhythmic. [94][95][96][97] These discrepancies arise because of differences in the protocol of sympathetic stimulation and dose of pharmacological agonists. These reports showed a protective effect of sympathetic activity in response to a progressive increase in adrenergic stimulation.…”
Section: Lqts3mentioning
confidence: 99%
See 3 more Smart Citations